Pendampingan Belajar Bahasa Inggris (Basic English) Pada Anak Usia Sekolah Dasar - Silva Azahra; Rihatul Jannah; Eneng Liah Khoiriyah; Eka Dewi Fithrotunisa; Minhatul Ma'arif (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Assistance in learning English for elementary school-age children is an important process in developing their langua2ge skills. This mentoring program is designed to introduce children to English in a fun and effective way. This includes the use of a variety of learning methods appropriate to the developmental level of the children. This English learning assistance for primary school age children aims to create a positive and fun learning environment, stimulate children's interest in English, and help them develop communication skills that will be useful throughout their lives. The method used is learning chili singing. This learning assistance is carried out 3 times in 1 week from 19.00 to completion. Based on the padaevaluation and observation results, there is an increase in student learning motivation and students' understanding of English.